COMPUTER GAME «FIRST MILLION» AS ELEMENT OF EDUCATIONAL ENVIRONMENT «ATOMIC PHYSICS» (Journal of Information Technologies in Education (ITE), 2011)
In this article possibility of application of computer games is exposed in an educational process from physics, attitudes of students of senior classes are investigational toward computer games.
Keywords: atomic physics; computer games; educational process